Study of baseline and postbronchodilator pulmonary function test and changes after treatment with two weeks of systemic steroid in presumed COPD cases. - Nepal, Manoj (2003)
ABSTRACT: Introduction:Chronic obstructive pulmonary disease is a leading cause of hospital admission and is also the leading cause of health care burden in our community, but pulmonary function is not done routinely either it is not available or no effort is done to separate other reversible causes of airflow limitation. Chronic airflow limitation may be caused by chronic bronchitis, emphysema, chronic asthma, bronchiectasis, cystic fibrosis, bronchopulmonary mycosis and central airway obstruction. Chronic bronchitis and emphysema is included under the broad heading of chronic obstructive pulmonary disease (COPD). Differentiation of asthma and COPD is very important from treatment point of view. Pulmonary function test usually differentiates these conditions and will optimize patient management. It is also seen that a diagnosis of chronic obstructive pulmonary disease is often made inappropriately when symptoms of asthma are mistakenly thought to be characteristic of COPD. One survey done in Nepal showed that there was some confusion among physicians about the term COPD. So use of the term COPD by physicians and prevalence of asthma among presumed COPD patients needed further investigation. Similarly one study done by SARA Study group in Italy found that Asthma in the elderly is frequently confused with COPD and is under diagnosed or misdiagnosed. That's why this study was done to see how many proportions of asthma patients were included under the term presumed COPD. Nepal Health Research Council approved this study. Objective : The Specific objective of the study was the following. A. To find out the proportions of asthma patients included under the term chronic obstructive pulmonary disease by demonstrating airway reversibility with bronchodilator and steroid. B. The General objectives of the study were: A. Correlation of reversibility of airway obstruction after bronchodilator and after steroid use. B. Correlation of different risk factors within this group. Design : Descriptive study of 104 consecutive presumed COPD cases selected from Br Hospital From November 2002 to March 2003 out of which four did not consent, 18 didn't report after antibiotic use, eight could not perform spirometery and 14 did not appear after the use of steroid for the second time for spirometery and were excluded or dropped during the study and only 60 patients were evaluated at the end of the study. Setting :Medical department and cardiology outpatient of Bir Hospital, a national postgraduate referral hospital Method:Consecutive patients who visited Bir Hospital outpatient, inpatient and emergency department were included in the study after consent and thorough evaluation including routine and laboratory check up involving chest X-ray and electrocardiogram was done. Echocardiogram was done whenever necessary. Pulmonary recordings taken by the investigator himself using vital graph models S -Vital graph limited maids moleton house Buckingham MK-18, serial no 47847. Sensitivity of the machine was tested with obtained pulmonary function data taken from other machines during pilot studies before this study. Inclusion criteria involved all those between the age range of 35 and 69 years who were presumed COPD, either history suggestive of chronic bronchitis or being treated as COPD for at least one year and not receiving inhaler or systemic steroid and having reduced FEVI (<80% of predicted). Exclusion criteria included clinical and ECG criteria of cor pulmonale and alternative diagnosis like bronchiectasis or lung fibrosis. Those showing acute bronchopulmonary infection were treated with antibiotic before enrolment and those not consenting for the study[ and failing to comply with steroid treatment along with sick who were unable to perform spirometry were also excluded. Parameters used were Forced Vital capacity (FVC), Forced expiratory volume in one second (FEV1), FEVI/FVC%, FEVI observed /FEVI predicted, FVC observed / FVC predicted. Patients were taught before proceeding to spirometry and recoding was done in sitting positing and making patient relaxed for sometime. Best curve out of a minimum of three curves with the difference of < 5% or 150ml whichever was smaller was selected. FEVI and FVC were recorded from best curve though it did not fall on the same graph. Reversibility test was done by using 200 microgram of salbutamol via metered dose inhaler with spacer and recording done after 30 minutes. All patients were prescribed prednisone 1 mg /Kg for two weeks and spirometric changes recorded. Result: More than 12% change in FEVl following 30 minutes of inhalation of 200 microgram of salbutamol via metered dose inhaler with spacer was found in 32 (53.33%) and more than 15% in 29 (48.33%) while more than 12% change in FEVI following oral steroid was in 36 (60%) and more than 15% was observed in 33 (55%). The difference in reversibility with bronchodilator and steroid was statiscally significant (p=0.002), which was statistically significant showed a highly significant correlation (¥=0.922), which was statistically significant (P=0.000). Mean reversibility in FEVI following 200-microgram inhalation with salbutamol via MDI (Metered dose inhaler) with spacer was 18.53%+-22.12 (Mean +-SD) with a range from -25% to 120% while mean change in FVC with salbutamol was 10.67%+-14.73 (Mean+-SD) with a range from -14.28% to 66.66%. Similarly corticosteroid reversibility with one milligram /Kg body weight of prednisolone for two weeks was a range from -44.44% tio 140%while similar change in FVC with steroid was 12.90%+-21.05 (Mean+-SD)with a range from -26.08%to66.66%. Smoking history in years had a mild negative correlation (¥=-0.339) with Obs FEVI/Obs FVC (p value = 0.262), which was statistically significant (P value = 0.043), while smoking history in years and amount of smoking did not show a statistical significant correlation with Obs FEVI or Obs FVC meaning thereby that most of the studied patients were having reversible airways disease. Conclusion : A large proportions of asthma patients were being included under the diagnonsis of presumed COPD. Thus our result suggests that Asthma is frequently confused with COPD or not diagnosed or mislabeled. These patients were thus being avoided the benefit of regular inhaled steroid. Regular spirometry and reversibility testing with steroid is advised to see the benefit of long-term inhaler steroid use in such patients.